Periodontal health and oral mucosal lesions as related to occupational exposure to acid mists - Vianna MIP, Santana VS, McKelvey W. (Blackwell Synergy, 2005)
The association between exposure to acid mists and periodontal changes and oral mucosal lesions was measured using data from an Oral Health Promotion Program in a large metal plant.